The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1175/jas-d-17-0111.1
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and Vertical Scaling of Cloud Geometry Inferred from CloudSat Data

Abstract: A method is described to characterize the scale dependence of cloud chord length using cloud-type classification reported with the 94-GHz CloudSat radar. The cloud length along the CloudSat track is quantified using horizontal and vertical structures of cloud classification separately for each cloud type and for all clouds independent of cloud type. While the individual cloud types do not follow a clear power-law behavior as a function of horizontal or vertical scale, a robust power-law scaling of cloud chord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
(75 reference statements)
3
17
0
Order By: Relevance
“…values reported in Table 1. Note that these values are similar to but not exactly the same as those calculated in Guillaume et al (2018), for which cloud length was derived from a 2-D curtain of cloud features. The main characteristic shared by all cloud types in Fig.…”
Section: Generalizing To All Scalessupporting
confidence: 69%
See 3 more Smart Citations
“…values reported in Table 1. Note that these values are similar to but not exactly the same as those calculated in Guillaume et al (2018), for which cloud length was derived from a 2-D curtain of cloud features. The main characteristic shared by all cloud types in Fig.…”
Section: Generalizing To All Scalessupporting
confidence: 69%
“…The cloud chord length was obtained at the cloud top (see Fig. 5) unlike that obtained in Guillaume et al (2018). frequency decrease for larger scales.…”
Section: Generalizing To All Scalesmentioning
confidence: 79%
See 2 more Smart Citations
“…Guillaume et al (2018) have shown that the distribution of horizontal cloud chord length evaluated from CloudSat data was heavily skewed toward short scales, so that clouds at the CloudSat horizontal resolution of 1.1 km are vastly more frequent than clouds at scales of about 2,000 km, which are very rare. From these data, we extracted nonoverlapping rectangular patches of radar reflectivity, 64 × 64 radar bins in size.…”
Section: Datamentioning
confidence: 99%